A Study on the Integration of ICT into Accounting Curriculum - Marjan Mohd Noor; Jaya Kumar Shanmugam; Sambas Ade Kesuma; Wan Kamarul Hazim Wan Ya (Journal of Management Research, 2024)
Purpose – This study provides an analysis view of prior studies on the integration of ICT into accounting curriculum. Methodology – The method of document analysis is used to collect the data published from 1981 to 2023 in the fields of social science, specifically focused on the study of information technology and accounting curriculum. Scope of the study – This study revolves around the analysis of the past trends of publication years, the most influential countries, the most research-active institutions and the most highly cited articles in research studies exploring the integration of ICT into accounting curriculum. Findings –From 1981 to 2023, there has been a noticeable and significant increase in research focusing on integrating ICT into the accounting curriculum. This trend reflects the growing recognition of the pivotal role that technology plays in modern accounting education and practice. Practical Implications – The increasing research on integrating ICT into the accounting curriculum underscores the critical need for accounting programs to adopt advanced technologies, enhancing students’ technical skills, job readiness, and alignment with industry standards, thereby maintaining educational institutions’ relevance and competitive edge. Originality/ Value – This study lies in its comprehensive analysis of how technological advancements have been progressively adopted in accounting education. It uniquely documents the evolution of educational practices in response to ICT, providing a historical perspective that underscores the growing importance of digital competencies for accounting professionals. It also offers valuable insights for educators, policymakers, and researchers, guiding future curriculum development to ensure accounting education remains relevant and prepares students for modern workforce demands.